2012
DOI: 10.1093/cid/cis299
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Hemolytic Uremic Syndrome in Children Infected With Escherichia coli O157:H7: A Multivariable Analysis

Abstract: Antibiotic use during E. coli O157:H7 infections is associated with a higher rate of subsequent HUS and should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
141
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(151 citation statements)
references
References 35 publications
5
141
0
5
Order By: Relevance
“…The single randomized controlled trial included, which did not influence the results, was of limited utility because the treatment was provided late (day 7), which is close to the median day of onset of HUS in many North American series [9,27]. We attempted to mitigate this weakness by addressing publication and selection biases and broadening our search criteria to identify all publications, even when antibiotic use and development of HUS was not the focus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The single randomized controlled trial included, which did not influence the results, was of limited utility because the treatment was provided late (day 7), which is close to the median day of onset of HUS in many North American series [9,27]. We attempted to mitigate this weakness by addressing publication and selection biases and broadening our search criteria to identify all publications, even when antibiotic use and development of HUS was not the focus.…”
Section: Discussionmentioning
confidence: 99%
“…By also not including the work of Carter et al [42], who reported that antibiotic therapy early in illness was associated with increased fatalities, we might have understated our conclusions. Finally, data extractors were not blinded to our hypothesis, and 1 member of our team has previously published in the field [11,27,38]; however, literature screening and data extraction were conducted independently by 3 individuals who had neither met, nor discussed manuscripts with the study's senior author (P. I. T.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are still many active substances in Daio, for example, rhein, which has Our results showed that the administration of a single dose of 200 mg/g AZM 6 h after inoculation with the bacteria was not effective in improving the survival rates of infected mice, but when combined with Daio once a day for two days, the survival rates improved and the number of viable bacteria in the feces significantly decreased. Antibiotic use during E. coli O157:H7 infections has been reported to be associated with a higher rate of subsequent HUS and should be avoided [25]. However, in the biggest outbreak of EHEC O104:H4 in Germany, treatment with AZM was associated with a lower frequency of long-term STEC carrier status [26].…”
Section: Discussionmentioning
confidence: 99%
“…2 We offered no specific objections to using azithromycin if decolonization was appropriate late in illness (that is, during or after hemolytic uremic syndrome [HUS]), but we did note that azithromycin might carry some risk of causing HUS if administered early in illness. 3 However, newly published data that associate short-course azithromycin with sudden cardiac death 4 prompt us to offer additional comment on the work by Nitschke and colleagues. Sudden deaths, quite plausibly caused by arrhythmias, represent approximately 10% of fatalities in patients with typical HUS, [5][6][7] and myocardial ischemia can complicate HUS, even in children.…”
mentioning
confidence: 99%